2020
DOI: 10.3390/molecules25245938
|View full text |Cite
|
Sign up to set email alerts
|

The Molecular and Pathophysiological Functions of Members of the LNX/PDZRN E3 Ubiquitin Ligase Family

Abstract: The ligand of Numb protein-X (LNX) family, also known as the PDZRN family, is composed of four discrete RING-type E3 ubiquitin ligases (LNX1, LNX2, LNX3, and LNX4), and LNX5 which may not act as an E3 ubiquitin ligase owing to the lack of the RING domain. As the name implies, LNX1 and LNX2 were initially studied for exerting E3 ubiquitin ligase activity on their substrate Numb protein, whose stability was negatively regulated by LNX1 and LNX2 via the ubiquitin-proteasome pathway. LNX proteins may have versatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 166 publications
(171 reference statements)
0
4
0
Order By: Relevance
“…The results of ssGSEA showed a signi cant correlation between KLF9 and hypoxia and apoptosis; therefore, the mechanism of apoptosis induced by ROS in patients with OA and the potential role of KLF9 in this process need to be further investigated. PDZRN4, a member of the PDZRN family, is more likely to function as an E3 ubiquitin ligase because of its multiple PDZ and RING structural domains (53). Current studies suggest that it may act as a tumor suppressor in a variety of cancers (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…The results of ssGSEA showed a signi cant correlation between KLF9 and hypoxia and apoptosis; therefore, the mechanism of apoptosis induced by ROS in patients with OA and the potential role of KLF9 in this process need to be further investigated. PDZRN4, a member of the PDZRN family, is more likely to function as an E3 ubiquitin ligase because of its multiple PDZ and RING structural domains (53). Current studies suggest that it may act as a tumor suppressor in a variety of cancers (54)(55)(56).…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the lack of phenotypic effect observed with MIB1 could be due to the presence of several functional and redundant genes in mammalian cells. LNX2 is also known to target Numb for proteasomal degradation, hence influencing the Notch signaling in cis [ 58 , 59 ]. However, the role of Notch in cytokinesis has never been highlighted, despite clearly modulating the fate of daughter cells during asymmetric division [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that CEP55 is not recruited to the midbody because of its disorganisation, probably concomitant with the degradation of its protein components. LNX1 and LNX2 are structurally similar and display common protein substrates for ubiquitination [ 59 , 63 , 65 ]. Recently, proteomic studies have evidenced their potential substrates such as MID1 and MID2, as well as KIF14 [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…LNX1 related protein, LNX2 is also reported to upregulate Wnt/beta-catenin pathway in colorectal cancers [13]. In addition, recent studies also showed the role of LNX1 in the nervous system and pathophysiological cell signaling [14,15].…”
Section: Introductionmentioning
confidence: 98%